Cooling Fan Uses the BLDC Motor - Van Dung Do; Van The Tran (Journal of Technical Education Science, 2025)
The article presents simulation results, experimental results, and calculations of temperature control via an NTC temperature sensor and then demonstrates Oled SH1106 using the I2C port for communication. The author uses a 12V/100W BLDC motor with a maximum speed of 5380rpm to replace a 12V/100W DC motor with a maximum speed of 2200rpm. The author uses Arduino to control the speed of the cooling fan and shows it through the OLED screen. The input of the control is an NTC-type temperature sensor. However, this control method is independent of the control on the vehicle’s control box. This may be a limitation, but this research mainly demonstrates the applicability of BLDC motors. Using the overview method of DC motors compared to BLDC motors, calculate the temperature to control BLDC motors to reduce the heat of internal combustion engines and electric motors on cars. Replacing DC motors with another motor is a step forward in the electric motor industry. BLDC motor is an option to replace the DC motor.